Financial Development and Growth in India : A Growing Tiger in a Cage? - Oura, Hiroko (IMF Working Papers; Working Paper ;, 2008)
This paper examines the efficiency of the different segments of India's financial system using firm-level data on corporate financing patterns. Firms are increasingly relying on external funds to finance their investment in most recent years. Empirical analyses indicate that (1) the financial system in India is not channeling funds into industries with higher external finance dependence; (2) the debt financing system does not allocate funds according to firms' external finance dependence, while equity financing system does; and (3) firms in an industry that are more dependent on external finance grow more slowly.